Case report: Double adjacent ventral slot in two medium-sized breed dogs - Cojocaru, Razvan Grigore; Sicoe, Bogdan; Gaspar, Cristina; Grigoreanu, Alexandra; Orghici, Gabriel; Tibru, Ioan; Lacatus, Radu (Frontiers in Veterinary Science, 2024)
Two medium-sized, 7-year-old dogs, with no previous history of pain, presented with acute neurologic symptoms consistent with intervertebral disk disease. Both cases had CT, where cervical pathology was identified. In one dog, the diagnosis was singular extensive cervical disk herniation with possible epidural hemorrhage and in the other, the diagnosis was multiple-site cervical disk herniation. The first dog, a Shar-Pei, underwent treatment with two standard adjacent ventral slots between the C4–C5 and C5–C6 intervertebral disk spaces and a fenestration between the C3 and C4 intervertebral disk spaces. The second case, a beagle, underwent a double adjacent standard ventral slot between the C5–C6 and C6–C7 intervertebral disk spaces. Both dogs recovered uneventfully after the surgery and showed no signs of recurrence during a 2-year follow-up period. This is the first detailed report of the use of a double adjacent ventral slot as a treatment for spinal decompression in medium-sized dogs with multiple-site spinal cord compression.